Capabilities and industrial competitiveness impact towards Private HEI performance in Malaysia - Norhaidah Ahmad; Nurazree Mahmud; Najihah Hanisah Marmaya (Human Resource Management Academic Research Society (HRMARS), 2023)
This study attempts to construct a measurement model for assessment purpose by using SMARTPLS 4 application in order to investigate relationship between Theory of Resources Capabilities and Theory of Industrial Competitiveness toward Private Higher Education Institution Performance in Malaysia. The questionnaire was sent to 109 respondents known as Edupreneurs using purposive sampling. The result of the measurement model shows that all 10 constructs of Resource Capabilities (Independent Variable 1), Industrial Competitiveness (Independent Variable 2), and Private Higher Education Institution Performance(Dependent Variable) meet the thresholds/minimum limits for Composite Reliability (CR) and Average Variance Extracted (AVE),with all CRs greater than 0.7 and all AVEs greater than 0.5. For discriminant validity, the values were less than 0.90, indicating that discriminant validity was also met. In summary, this study contributes to the methodology by helping to develop questions in the survey, identifying the basic assumptions in the area of PHEI performance, demonstrating the validity of the items used, and showing how it can be applied to PHEI strategies in the future.